2005
DOI: 10.1089/end.2005.19.1199
|View full text |Cite
|
Sign up to set email alerts
|

Photoselective Vaporization of the Enlarged Prostate with KTP Laser: Long-Term Results in 240 Patients

Abstract: High-power photoselective KTP laser vaporization prostatectomy is feasible and appears to be safe and effective for immediate relief of the bladder-outlet obstruction secondary to benign hyperplasia. The system is a promising alternative in all, but especially in high-risk patients receiving anticoagulant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 19 publications
3
33
0
2
Order By: Relevance
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23] Collectively, they represented a total of 1376 PVP procedures.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23] Collectively, they represented a total of 1376 PVP procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Une série a inclus des patients ayant un volume prostatique supérieur à 60 mL, avec des résultats satisfaisants, tant en post-opératoire que 12 mois après le traitement [97]. Trois séries ont étudié des patients sous traitement anticoagulant : elles n'ont rapporté aucun cas de transfusion liée à une hémorragie peropératoire [104][105][106]. Enfin, une série a comparé des patients présentant ou non une rétention urinaire réfractaire pré-opératoire : la technique semblait efficace pour tous les patients, avec un taux de complications observé identique dans les deux groupes [108].…”
Section: Discussionunclassified
“…24 Retrograde ejaculation (33%) is the most common complication in most long term reports, however transfusion is rarely necessary and reoperation rates are 0∼7% at 5 years. [25][26][27] The newer 120 W HPS lasers have yet to report long term results. Recent reports of 120 W laser, however, suggested that the high power also resulted in decreased hemostatic ability.…”
Section: Prostate Lasersmentioning
confidence: 99%